Gender disparities in the application of public-access AED pads among OHCA patients in public locations. (May 2020) - Kiyohara, Kosuke; Katayama, Yusuke; Kitamura, Tetsuhisa; Kiguchi, Takeyuki; Matsuyama, Tasuku; Ishida, Kenichiro; Sado, Junya; Hirose, Tomoya; Hayashida, Sumito; Nishiyama, Chika; Iwami, Taku; Shimazu, Takeshi
Abstract: Background: Female out-of-hospital cardiac arrest (OHCA) patients have been reported to be less likely to receive cardiopulmonary resuscitation by bystanders compared with male patients in prehospital settings. However, no clinical studies have investigated gender disparities in the application of public-access automated external defibrillator (AED) pads among OHCA patients in public locations. Methods: OHCA data from 2011 to 2018 were obtained from the OHCA registry in Osaka City, Japan and OHCAs that occurred in public locations were included. Gender differences in receiving public-access AED pad application by bystanders were assessed according to the age of the OHCA patient (<15, 15–49, 50–74, and ≥75 years) after controlling confounders. Results: The analysis included 4358 OHCA patients (3313 male and 1045 female patients). The multivariable logistic regression analyses found no significant gender differences in the likelihood of public-access AED pad application among patients aged <15 years (5.3% in male patients vs 6.3% in female patients; adjusted OR = 1.00, p = 1.000), 50–74 years (16.8% vs 12.7%; adjusted OR = 0.96, p = 0.796), and ≥75 years (12.3% vs 14.8%; adjusted OR = 1.45, p = 0.098). In contrast, among patients aged 15–49 years, female patients were significantly less likely to receive public-access AED pad application compared with male patients (12.1% vs 5.2%; adjusted OR = 0.54, p = 0.032). Conclusion: In this population, female OHCA patients of reproductive age (15–49 years) were less likely to receive public-access AED pad application compared with male patients of the same age group.